Time-Dependent Changes in Cortisol and Tympanic Temperature Lateralization During Food Deprivation Stress in Marmoset Monkeys - Pereira, Lucas C.; Maior, Rafael S.; Barros, Marilia (Frontiers in Behavioral Neuroscience, 2020)
Temporal information about food availability can be easily entrained, as in the case of fixed feeding routines of captive animals. A sudden unintentional or deliberate delay (e.g., food deprivation - FD) leads to frustration and psychological stress due to the loss of temporal predictability. How marmosets – an increasingly used small primate – process and respond to FD stress has not been previously assessed. Here we delayed the routine feeding of adult captive marmosets for 3 or 6 h. Blood cortisol concentration was used as a hormonal measure of the stress response. Changes in the left/right baseline tympanic membrane temperature (TMT) were used as an indirect ipsilateral indicator of hemisphere activity. Marmosets that were deprived for 3 h had higher cortisol levels than non-deprived controls. Cortisol concentration in the marmosets deprived for 6 h did not differ from controls possibly due to adaptative mechanisms against the detrimental effects of prolonged high cortisol levels. Interestingly, FD stress may have been processed more symmetrically at first, as indicated by the bilateral increase in TMT at the 3 h interval. As the event progressed (i.e., 6 h), a clear rightward TMT bias suggests that hemisphere activity had become asymmetrical. Therefore, the sudden loss of temporal predictability of an entrained routine feeding schedule induces time-dependent changes in the cortisol stress response and shifts in the TMT (and potentially hemisphere activity) lateralization bias of adult captive marmosets.